Best Answer

(4 + 2x) - (-2x + 1) = 13 + 6

4 + 2x + 2x -1 = 19

4x +3 = 19

4x = 19 - 3

4x = 16

therefore x = 16/4

x = 4

Study guides

☆☆

Q: 4 plus 2x- -2x plus 1 equals 13 plus 6?

Write your answer...

Submit

Still have questions?

Related questions

The answer to 1 over 2x plus 13 equals 9 is x equals -8.

2x + 1 = 13; 2x = 12; x = 6

2x plus 3y

4+2x-2x+1=13+6 Combine like terms. (4+1=5; 2x-2x=0; 13+6=19) 5=19 This problem has no solution.

84

x=1

x = 0

3x+1+2x-2 = 64 3x+2x = 64-1+2 5x = 65 x = 13

-2x plus 3y equals 1

x = 8, y = -1

Y = 2x + 1

NM equals 2x + 1, as stated in the question!

People also asked

Featured Questions